PENGARUH KUALITAS PRODUK, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KARTU XL BUSINESS SOLUTION PADA PT. ACTIVATE ASIA - Lucy Nancy Simatupang; Syarah Afriyani (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2021)
This study aims to determine the effect of product quality, promotion and brand image on the decision to purchase XL Business Solution cards at PT. Activate Asia. This research is a causal research, the population in this study are employees of PT. Activate Asia, which uses the XL Business Solution card, totaling 130 employees. The sampling technique is probability sampling and uses the Slovin formula to produce 98 samples. The data analysis method used in this study is multiple linear regression analysis by performing instrument tests, classical assumption tests and hypothesis testing with the help of SPSS 23 software. The results show that simultaneously the variables of product quality, promotion and brand image have a significant effect on purchasing decisions. And partially the variables of product quality, promotion and brand image have a significant effect on purchasing decisions